2012
DOI: 10.1016/j.marpol.2011.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of deep-sea fisheries

Abstract: As coastal fisheries around the world have collapsed, industrial fishing has spread seaward and deeper in pursuit of the last economically attractive concentrations of fishable biomass. For a seafood-hungry world depending on the oceans' ecosystem services, it is crucial to know whether deep-sea fisheries can be sustainable.The deep sea is by far the largest but least productive part of the oceans, although in very limited places fish biomass can be very high. Most deep-sea fishes have life histories giving th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
190
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 287 publications
(199 citation statements)
references
References 78 publications
3
190
0
6
Order By: Relevance
“…There is an ongoing concern that seamount stocks are overfished, and fishing is impairing the benthic communities (e.g. Clark 2001;Clark and Koslow 2007;Clark and Rowden 2009;Clark et al 2006;Norse et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There is an ongoing concern that seamount stocks are overfished, and fishing is impairing the benthic communities (e.g. Clark 2001;Clark and Koslow 2007;Clark and Rowden 2009;Clark et al 2006;Norse et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…An evaluation of fishing sustainability is needed to know which are the main aspects influencing the depletion of marine resources. Therefore, recovery of marine ecosystems is essential to achieve oceans sustainability [2][3][4][5]. A study developed by Swartz et al [6] showed that the worldwide development of marine fisheries through the past years was conducted by a continuous exploitation of new fishing sites.…”
Section: Introductionmentioning
confidence: 99%
“…Such increased activity tends to consume a considerable fraction of food energy and compromise somatic growth and reproduction, typically low and inefficient among seamount fish. In a sense, seamount fishers, while selecting firm-textured flesh fishes, are taking advantage of particular deep seamount selective pressures, which in turn also favour life-history features that limit opportunities for productive and sustainable catches (Norse et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, this contribution has been sustained by intense harvesting of coastal, productive and accessible resources. However, because these resources have been exhaustively exploited and demands for marine products have increased by the world's growing population, fisheries globally expanded seaward, to remote deep areas (Pauly et al, 2005;Morato et al, 2006;Norse et al, 2012). Such expansion was initially driven by the search for better catches of shelf demersal resources in the rim of the continental margin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation